Outcome of pulpotomy in permanent teeth with irreversible pulpitis: a systematic review and meta-analysis - Amber Ather; Biraj Patel; Jonathan A. L. Gelfond; Nikita B. Ruparel (Scientific Reports, 2022)
Abstract Treatment planning is key to clinical success. Permanent teeth diagnosed with “irreversible pulpitis” have long been implied to have an irreversibly damaged dental pulp that is beyond repair and warranting root canal treatment. However, newer clinical approaches such as pulpotomy, a minimally invasive and biologically based procedure have re-emerged to manage teeth with pulpitis. The primary aim of the study was to conduct a meta-analysis to comprehensively estimate the overall success rate of pulpotomy in permanent teeth with irreversible pulpitis as a result of carious pulp exposure. The secondary aim of the study was to investigate the effect of predictors such as symptoms, root apex development (closed versus open), and type of pulp capping material on the success rate of pulpotomy. Articles were searched using PubMed, Scopus, CENTRAL, and Web of Science databases, until January 2021. Outcomes were calculated by pooling the success rates with a random effect model. Comparison between the different subgroups was conducted using the z statistic test for proportion with significance set at alpha = 0.05. A total of 1,116 records were retrieved and 11 studies were included in the quantitative analysis. The pooled success rate for pulpotomy in teeth with irreversible pulpitis was 86% [95% CI: 0.76–0.92; I 2 = 81.9%]. Additionally, prognostic indicators of success were evaluated. Stratification of teeth based on (1) symptoms demonstrated that teeth with symptomatic and asymptomatic irreversible pulpitis demonstrated success rate of 84% and 91% respectively, with no significant difference (p = 0.18) using z-score analysis; (2) open apex teeth demonstrated a significantly greater success rate (96%) compared to teeth with closed apex (83%) (p = 0.02), and (3) pulp capping materials demonstrated that Biodentine yielded significantly better success rates compared to Mineral Trioxide Aggregate (MTA), calcium hydroxide, and Calcium Enriched Mixture (CEM.) Collectively, this is the first meta-analytical study to determine the clinical outcome of pulpotomy for carious teeth with irreversible pulpitis and it’s predictors for success. Moreover, we identify the stage of root development and type of biomaterial as predictors for success of pulpotomy.